Español Behind the Scenes: Stress and Resilience in Peruvian Nurses during the COVID-19 Era - Terrones Marchena, Natali (2024)
The purpose of this research was to establish the relationship between work stress and resilience during the period of the COVID-19 pandemic in Peruvian nurses, using a correlational design. The sample consisted of 112 nurses whose ages ranged from 22 to 60 years, selected by non-probabilistic sampling. The findings revealed a significant and inverse correlation between job stress and resilience, indicating that the lower the level of job stress, the higher the resilience manifested by the individual (r = -0.31; p < 0.05). After analyzing the results, it was observed that the stress level predominated in 33%, while the low resilience level prevailed in 37.5%. In conclusion, it was inferred that individuals who approach their life in an assertive and persevering manner are likely to experience less stress and are able to cope with challenges and obstacles in a positive way along their trajectory.